Telenursing for Cancer Early Detection and Prevention - Nurhesti, Putu Oka Yuli; Adiputra, Putu Anda Tusta; Kamayani, Made Oka Ari; Prapti, Ni Ketut Guru (Journal of A Sustainable Global South; Vol 7 No 2 (2023): August 2023, 2023)
Abstract The increasing incidence and prevalence of cancer in the world is a global problem that requires definitive efforts to prevent it through community empowerment. The 2018 cancer incidence rate in the world is 14.1 million cases with a death rate of 8.2 million and this figure is expected to continue to increase every year. The prevalence of cancer in the province of Bali is 2.3%, this incidence continues to increase. Prevention and early detection of cancer will reduce both cancer morbidity and mortality. The purpose of this activity is to empower the community through the utilization of science and technology and telenursing in the prevention and early detection of cancer in Kedisan Village, Tegalallang, Gianyar. The method used is training and simulation of the use of virtual meeting media regarding the prevention and early detection of cancer in youth committee members and members. The results of the activity show that there is a significant difference in the knowledge of respondents before and after training and simulation with a value of p = 0.001, there is an increase in knowledge before and after training and simulation. This method can be a community empowerment method in preventing cancer, especially in the younger generation. Cancer prevention can be done by conducting cancer prevention training and simulations using various virtual methods   Index Terms — prevention, early detection, cancer, telenursing